2009
DOI: 10.1108/02635570911002306
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of satisfaction and continuance intention towards self‐service technologies

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
162
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(210 citation statements)
references
References 52 publications
16
162
0
6
Order By: Relevance
“…A user's perceived usefulness towards an IS will affect their level of satisfaction and IS continuance intention. The five hypotheses in ECM-ISC have been supported by a large number of empirical studies, for which the research topics have not been limited to e-learning, but have also involved the issues of IS continuance in other areas [13,14]. The current study proposes the following five hypotheses according to ECM-ISC:…”
Section: Research Hypotheses and Conceptual Modelmentioning
confidence: 98%
“…A user's perceived usefulness towards an IS will affect their level of satisfaction and IS continuance intention. The five hypotheses in ECM-ISC have been supported by a large number of empirical studies, for which the research topics have not been limited to e-learning, but have also involved the issues of IS continuance in other areas [13,14]. The current study proposes the following five hypotheses according to ECM-ISC:…”
Section: Research Hypotheses and Conceptual Modelmentioning
confidence: 98%
“…Não obstante, autores acreditam que a prontidão tecnológica influencia, além da satisfação, a intenção comportamental dos usuários (Lin & Hsieh, 2007), especialmente, a intenção de uso continuado (Chen, Chen & Chen, 2009;Son & Han, 2011). Bhattacherjee (2001) propõe, ao analisar estudos de aceitação da tecnologia, que a viabilidade de um SI em longo prazo e seu eventual sucesso depende da sua continuidade de uso mais do que seu primeiro uso.…”
Section: Hipóteses Do Estudounclassified
“…A satisfação com a tecnologia é antecedente da intenção de continuidade de uso (hipótese 9), apresentando uma relação de grau de 19,3%. Essa constatação corrobora estudos anteriores, que abordam a continuidade de uso como consequente da satisfação com a tecnologia (Bhattacherjee, 2001;Chen, Chen & Chen, 2009;Fialho, Löbler & Lütz, 2010). Dessa forma, ao se alcançar a satisfação com a tecnologia, os indivíduos continuam a utilizá-la, o que pode levar a comportamentos de lealdade do cliente (Fornell, 1996;Szymanski & Henard, 2001 O estudo apresenta limitações referentes à amostra ser formada apenas por universitários e embora a escala de prontidão tecnológica (TRI) já ter sido utilizada no contexto nacional, nota-se carência de trabalhos com foco único em sua validação e melhoria e que combinem os construtos da escala com constructos de outros modelos.…”
Section: Hipóteses Do Estudounclassified
See 1 more Smart Citation
“…As a consequence, many studies have suggested that TAM should be enhanced to produce a more inclusive model. It's likely that those studies with a focus on the integration of TAM with Technology Readiness (Lin, Shih, & Sher, 2007;Godoe & Johansen, 2012) and TAM with the Theory of Planned Behavior (Chen, Chen, & Chen, 2009;Lee, 2009) have the most appeal. Because of this, the TAM model has been customized and tweaked for specific cases.…”
Section: Conceptual Modelmentioning
confidence: 99%